The impact of testosterone levels on J-wave patterns observed in healthy Turkish males - Hünük, Burak (The European Research Journal, 2020)
Objectives: Early-repolarization (ER) and Brugada-type-ECG-patterns (BTEP) have recently been grouped under a common terminology called “J-wave patterns” (JWP) and have been associated with an increased risk of sudden-cardiac-death. Scarce data is present about the male dominance in JWP and the probable effects of gonadal hormones on cardiac ion-channel functions. We sought to evaluate the relationship of testosterone-levels and the presence of JWP in healthy Turkish-males. Methods: One hundred eighty-five healthy male volunteers between ≥18 to ≤50 years old without any cardiac disorders were evaluated. ECG, blood biochemistry and total testosterone levels were obtained together with thorough physical examination. Subjects with complete-bundle-branch-block, non-sinus-rhythms and any abnormality on cardiac examination were excluded from the study. BTEP was searched according to the EHRA/HRS 2016 Consensus Conference on V1-V3. ER on ECG was defined as J-point elevation of ≥ 0.1 mV in ≥ 2 leads in the inferior (II, III, aVF) (Inferior ER), lateral (DI, aVL, V4-6) (Lateral ER) or both (Inferolateral ER). Results: A total of 179 subjects (mean age 34.9 ± 7.9 years) were included in our analyses. Three BTEP (1.7%) and 45 ER (26%) were detected. 22 were lateral (49%), 13 inferior (29%) and 10 were (22%) inferolateral ER. JWP (+) subjects (n = 48, 27%) were demonstrating significantly lower basal heart rates (73.9 ± 11bpm vs 68.4 ± 10.3 bpm, p = 0.001) and longer PR intervals (153.9 ± 20.3 ms vs 163.3 ± 21.6 ms, p = 0.01). JWP (+) subjects had significantly higher testosterone levels compared with the ones without (485.5 ± 128.3 ng/dl vs 559.3 ± 167.7, p < 0.001). In the subgroup analyses, BTEP and inferior/inferolateral ER patterns were significantly associated with higher testosterone levels compared with the JWP (-) population, while testosterone levels of subjects with lateral ER was not significantly higher. Electrolytes and blood chemistry values were non-significant between JWP + and - subjects. In the ROC analysis, the cut-off value for predicting the presence of a JWP on ECG was 629 ng/dl with a sensitivity of 44% and specificity of 86% [AUC = 0.66 (95% CI: 0.56-0.75), p = 0.001]. In multivariate analysis, total testosterone level > 629 ng/dl was significantly predicting a JWP on ECG, even outperforming age and hs-CRP levels with an OR of 4.57 (95% CI 1.910-10.9, p = 0.001). Conclusions: Testosterone might be associated with the male predominance observed in the JWP. More malignant inferior/inferolateral ER seems to be mainly associated with the high testosterone levels in Turkish male population. This finding might be attributed to the previously demonstrated effects of testosterone on cardiac ion-channel functions, especially outward-K channels.